On Wind Turbine Power Delta Control - Iker Elorza; Carlos Calleja; Aron Pujana-Arrese (Energies, 2019)
One of the major challenges facing wind energy at the moment is its dependence on dispatchable energy sources to match power supply to demand and provide an adequate spinning reserve. There is no fundamental impediment for this to be done with wind energy when wind conditions are such that sufficient wind power is available. It is, in fact, common for wind farms to participate in primary and secondary frequency regulation via droop curves, curtailment, synthetic inertia, proportional de-loading, and delta control. However, although the literature presents several approaches to turbine-level control functions of this sort, it is not trivial to extract from it a readily industrializable set of algorithms. Said extraction, focused on delta control and the addition of our own contributions, is the purpose of this paper, where we propose an extension of popular torque and pitch control algorithms, which allows delta control without the wind speed observers used by other authors.